Insights into the photocatalytic role of glycine-assisted sol-gel auto-combustion synthesized (Co, Mn)(Co, Mn)2O4 nanostructures for efficient visible light-driven degradation of methyl orange - Ghazal Oroumi; Foroozan Samimi; Makarim A. Mahdi; Elmuez A. Dawi; Masoud Salavati-Niasari (Arabian Journal of Chemistry, 2024)
Research on the use of new materials and the improvement of existing fast ways for removal of water pollutants is still challenging. This work documented rational fabrication of (Co, Mn)(Co, Mn)2O4 nanoparticles as nano-photocatalyst materials with improved charge carrier separation and strong redox potential for efficient degradation of methyl orange (MO) in wastewater. This investigation illustrated that the Co/Mn molar ratio can greatly affect the textural and structural properties. From the point of view of size and shape, the optimum product with 1:3 M ratio of Co to Mn precursors was selected as a catalyst in the photocatalysis process. The prepared highly crystallized phase of tetragonal (Co, Mn)(Co, Mn)2O4 describe an optical band gap of 1.7 eV, according to the DRS data, which make them as efficient visible driven photocatalysts. The photodegradation experiments of spinel mixed structures were assessed by investigation of photocatalyst dosages and initial MO concentrations to unravel how these operational parameters affect Co-Mn-O photocatalysis. A remarkable discoloration capability of 68.07 % could result from the catalyst dosage of 0.04 g and dye concentration of 15 mg/L after 120 min of visible light. The kinetics survey further unveiled the maximum rate constant of 0.0080 min−1 for the MO degradation. In the scavenger trials, singlet oxygen (1O2) and superoxide (●O2−) radicals were principal reactive oxygen species (ROS) responsible for pollutant photodegradation in the presence of pure (Co, Mn)(Co, Mn)2O4 structures. In addition, the cyclic performance of catalyst depicted a removal efficiency of 60.1 % over 5 runs.